Salmonella Hepatitis in Children : An Update - Kadir, Sadika; Begum, Tamanna; Islam, Md Rafiqul; Nabi, Golam; Haque, Md Ashraful; Hoque, Naima Sharmin; Yasmeen, BH Nazma (Northern International Medical College Journal, 2020)
Salmonella hepatitis is one of the atypical presentations of typhoid fever and can be defined as reversible involvement of liver during the course of typhoid fever. There have been more than 150 cases of salmonella hepatitis reported both in developed and developing countries. The documented incidence varies widely from 1 to 26% of patients with Typhoid fever. It presents with jaundice and tender hepatosplenomegaly. Investigation shows slightly raised transaminase levels with or without 5 adenosine neucleosidase and or decreased prothombin time index. It complicates into hepatic encephalopathy and bleeding diathesis. A positive culture for Salmonella from blood or stool is essential to differentiate Salmonella hepatitis from other causes of acute hepatitis. Hepatic pathology is characterized by the presence of typhoid nodules with marked hyperplasia of reticuloendothelial system. The ALT/LDH ratio < 9 is suggestive of Salmonella hepatitis which is > 9 in viral hepatitis. The prognosis is usually good as Salmonella hepatitis responses with specific antibiotic therapy and jaundice resolves with clinical improvement. The clinical course can be severe with high mortality (20%) sometime. In our country where enteric fever is endemic, the recognition of Salmonella hepatitis is of clinical importance . Northern International Medical College Journal Vol.10 (2) Jan 2019: 397-399